Advancing transformative adaptation through social equity: Land, water and food systems in the Global South - Fisher, Eleanor; Hellin, Jon; Ng'endo, Mary (Elsevier, 2025)
The Virtual Special Issue: Social Equity published by Current Research in Environmental Sustainability focuses on the importance of social equity for climate adaptation in land, water and food systems in the Global South. Emphasizing that theory is ahead of practice and that empirical examples are vital for learning, we introduce the set of articles, which each present the results of empirical research relevant to equity considerations. The papers demonstrate how vital is transdisciplinary research that engages critical social science perspectives and addresses how different actors give meaning to social equity, fairness and justice based on their experiences and lived realities. Taken together, they reinforce the need for further learning on how social equity can be fostered within transformative adaptation.